2006
DOI: 10.1111/j.1464-410x.2006.06141.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the overactive bladder on health‐related utility and quality of life

Abstract: status, frequency, urgency, and stress incontinence. RESULTSOf 2193 surveys dispatched, 609 (27.8%) were returned; of these patients, 52% had incontinence, of whom 83% had both frequency and urgency, and 60% stress incontinence. Patients with stress incontinence reported a mean ( SD ) EQ5D index of 0.578 (0.331), compared to 0.714 (0.281) for all other patients ( P < 0.001). From the SF36, respondents scored lowest in the role physical domain and highest in the mental domain, with mean scores of 33.8 and 72.1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 21 publications
(26 reference statements)
6
65
0
4
Order By: Relevance
“…Their findings are consistent with several other studies such as [6,9,14,15,25,29,30]. They found that urinary incontinence has more widespread negative effects on quality of life.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Their findings are consistent with several other studies such as [6,9,14,15,25,29,30]. They found that urinary incontinence has more widespread negative effects on quality of life.…”
Section: Discussionsupporting
confidence: 82%
“…Individuals with UI do not always seek medical help [9]. There is a misconception that the condition cannot be treated [13,14]. UI is not life threatening [8], does not lead to death [15] but the symptoms often impair the social, physical and psychological well-being of affected individuals [16].…”
Section: Introductionmentioning
confidence: 99%
“…Tali pesi sono definiti in funzione di un indice di patologia combinato, dato dalla somma dei singoli indici di incontinenza e [21] frequenza. Gli Autori del modello originario hanno ottenuto tali pesi correlando i sintomi urinari con i punteggi del questionario EQ-5D somministrato a 461 pazienti svedesi con OAB (continenti e incontinenti) arruolati in uno studio di Willingness To Pay [20] (Tabella IV).…”
Section: Qualità DI Vitaunclassified
“…Gli Autori del modello originario hanno ottenuto tali pesi correlando i sintomi urinari con i punteggi del questionario EQ-5D somministrato a 461 pazienti svedesi con OAB (continenti e incontinenti) arruolati in uno studio di Willingness To Pay [20] (Tabella IV). I dati originari sono stati rielaborati sulla base di un più recente studio di popolazione inglese condotto su 609 soggetti con OAB [21] …”
Section: Qualità DI Vitaunclassified
“…In recent years many researchers have focused on the evaluation of Health Related Quality of Life (HRQOL) in persons with UI, including their psychosocial functioning, broadly understood www.intechopen.com (Sutherst & Brown, 1980;Norton, 1982;Norton et al, 1988;Grimby et al, 1993;Grimby et al, 1997;Samuelsson et al, 1997;Wyman et al, 1997;Wyman, 1998;Chiarelli et al, 1999;Kelleher et al, 1997;Swithinbank & Abrams, 1999;Brown et al, 1999;Coyne et al, 2000;Kelleher, 2000;Coyne et al, 2003;Fultz & Herzog, 2001;Badia et al, 2004;Currie et al, 2006;Bidzan, 2008;Bidzan, 2011). It should be emphasized in this context that the evaluation of HRQOL has become in recent times the most important diagnostic and prognostic index for the functioning of patients, regardless of the disease (Majkowicz et al, 1997;Brown et al, 1999a;Swithinbank & Abrams, 1999;Woodman et al, 2001), and is recommended by the International Continence Society Williams, 2004).…”
Section: Introductionmentioning
confidence: 99%